FT-IR spectromicroscopy of mammalian cell cultures during necrosis and apoptosis induced by drugs. Issue 5 (2010) - Lamberti Lamberti, Annalisa Annalisa; Sanges Sanges, Carmen Carmen; Arcari Arcari, Paolo Paolo
Abstract : FT-IR is used in the field of biology and medicine to detect bimolecular changes in disordered cells and tissues. In this report, using FT-IR microscopy, we characterize changes in apoptotic and necrotic Jurkat cells with respect to normal cells. The analysis of deconvoluted regions of the FT-IR spectra showed significant differences compared to the controls in three spectral regions. In particular, the apoptotic cells were characterized by an increase in the absorption at 2925 cm −1, due to the asymmetric CH2 -stretching ( ν as CH2 ) of membrane lipids whereas the spectral areas ratio (A1654 /A1629 ) of the amide I region indicated an increase in apoptotic cells of more α-helical structures with respect to of β -sheet content. Interestingly, apoptotic cells showed the appearance of a peak around 1743 cm¯ 1, ν (C=O) assigned to acid ester. Because no other similar increase for lipid bands was observed, the increase of A1745 is not simply due to an increase in the number of lipid molecules or their density but could also be indicative as marker of apoptosis. These spectral changes were not observed in necrotic Jurkat cells.